Faktor Penentu Keterlibatan Siswa di Sekolah Menengah: Sebuah Kajian Tinjauan Sistematis - Bintang Lestyasari; IGAA Noviekayati; Suhadianto Suhadianto (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
Student engagement refers to students’ motivation to participate in the learning process such as behaviour, cognitive, and emotional. According to Self-Determination Theory, individuals are motivated to engage in an activity when their basic psychological needs include autonomy, competence, and relatedness. This study aims to identify, classify, and synthesize various factors that contribute to student engagement at the secondary education level (junior high and senior high school). This study employs a systematic literature review design based on PRISMA guidelines, with articles retrieved from four data sources namely Google Scholar, ScienceDirect, PubMed, and Garuda. Of the 1,187 articles found, 25 met the criteria and were analyzed in depth. The results of the analysis show that the factors contributing to student engagement are grouped into three main themes: personal, interpersonal, and school environment factors. One of dominant personal factors predicting student engagement is self-efficacy. The most dominant interpersonal factors as predictors were parental support, peer support, and teacher-student interactions. School environmental factors that served as predictors of student engagement included school climate, school well-being, and school moral engagement.